Association of Serum Ferritin Levels With Obstructive Sleep Apnea in Overweight/Obese US Populations: A Population-Based Study From the NHANES - Zhang Y; Zhou P; Xu C; Su H; Li R; Sun L; Yang Y (Nature and Science of Sleep)
Yang Zhang,1,* Pinglang Zhou,2,* Chuan Xu,3,* Hua Su,1 Rendong Li,1 Longhua Sun,2 Yihan Yang1 1Jiangxi Provincial Key Laboratory of Respiratory Diseases, Jiangxi Institute of Respiratory Diseases, The Department of Respiratory and Critical Care Medicine, The First Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, 330006, People’s Republic of China; 2The Department of Respiratory and Critical Care Medicine, The First Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, 330006, People’s Republic of China; 3Department of Thoracic Surgery, The First Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, Jiangxi, 330006, People’s Republic of China*These authors contributed equally to this workCorrespondence: Yihan Yang, Jiangxi Provincial Key Laboratory of Respiratory Diseases, Jiangxi Institute of Respiratory Diseases, The Department of Respiratory and Critical Care Medicine, The First Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, 330006, People’s Republic of China, Email yangyihan@email.ncu.edu.cn Longhua Sun, The Department of Respiratory and Critical Care Medicine, The First Affiliated Hospital, Jiangxi Medical College, Nanchang University, Nanchang, 330006, People’s Republic of China, Email ndyfy05715@ncu.edu.cnObjective: To investigate the relationship between serum ferritin levels and OSA in overweight/obese individuals and assess the association between ferritin levels and all-cause mortality in overweight/obese female OSA patients.Methods: Cross-sectional (n = 4,809) and prospective (n = 832) data from overweight/obese adults from the 2005– 2008, and 2015-March 2020 NHANES cycles were analyzed. Participants were categorized into quartiles (Q1-Q4) based on their ln-transformed serum ferritin levels. Multivariable logistic regression and restricted cubic spline regression (RCS) investigate associations. Kaplan-Meier survival analyses and Cox proportional hazards regression examined the relationship between ferritin levels and all-cause mortality in OSA patients.Results: After adjusting for potential confounding factors, we found that ln-transformed ferritin levels were associated with an increased risk of OSA (Q4 vs Q2: OR = 1.07, 95% CI: 1.01– 1.13, P = 0.020, P for trend = 0.010). A non-linear U-shaped association was observed between ferritin levels and OSA risk (P-non-linear = 0.029), with an inflection point at ln-transformed ferritin of 4.58 (corresponding to a serum ferritin concentration of 97.51 ng/mL). In female OSA patients, elevated ferritin levels were associated with increased all-cause mortality risk (Q4 vs Q2: HR: 5.46, 95% CI: 1.18– 25.16, P = 0.029, P for trend = 0.032).Conclusion: Ferritin levels in overweight/obese individuals show a U-shaped relationship with OSA risk, and elevated levels correlate with increased all-cause mortality in female overweight/obese OSA patients. In the future, further research is needed to explore the potential associations between ferritin, inflammation, obesity, and OSA.Keywords: ferritin, obstructive sleep apnea, overweight/obese, all-cause mortality, NHANES